Metabolisen oireyhtymän riskitekijöiden yhteys naisten epigeneettiseen vanhenemiseen - Orell, Virpi (2025)
Orell, V. 2025. The association between metabolic syndrome risk factors and epigenetic aging among women. Faculty of Sport and Health Sciences, University of Jyväskylä, Gerontology and Public Health, Master’s thesis, 40 pages.